Wired for thought : how the brain is shaping the future of the internet - Stibel, Jeffrey M. (Harvard Business School Press, 2009)
In this age of hypercompetition, the Internet constitutes a powerful tool for inventing radical new business models that will leave your rivals scrambling. But as brain scientist and entrepreneur Jeffrey Stibel explains in Wired for Thought, you have to understand its true nature. The Internet is more than just a series of interconnected computer networks: it's the first real replication of the human brain outside the human body. To leverage its power, you first need to understand how the Internet has evolved to take on similarities to the brain. This engaging and provocative book provides the answer. Stibel lays out: - How networks have changed and what that implies for how people connect and form communities - What the Internet-and online business opportunities-will look like in the future - What the next stage of artificial intelligence will be and what opportunities it will present for businesses Stibel shows how exceptional companies are using their understanding of the Internet's brainlike powers to create competitive advantage-such as building more effective Web sites, predicting consumer behavior, leveraging social media, and creating a collective consciousness.